(untitled) (Research, Society and Development, 2023)
Depression manifests as a set of symptoms that compromise an individual’s quality of life. Due to the lack of success certain treatments in some patients, injections of botulinum toxin in the glabellar region have become a potential alternative to help alleviate symptoms associated with the psychiatric disorder. This is an integrative review on the use of botulinum toxin in the treatment of depression. We conducted a cross-referencing of the descriptors "Botulinum Toxin,"Depression, "Emotions," "Facial Feedback," and "Self-esteem" in the following databases: Scientific Electronic Library Online (Scielo), National Library of Medicine (PubMed MEDLINE), and Google Scholar. The location of BoNT/A facial injections is relevant to the success of depression treatment. Glabellar BoNT injections can reduce symptoms of mild to moderate depression. Botulinum toxin can also influence the proprioception of emotions, according to the facial feedback theory. Adverse effects associated with BoNT are generally mild and transiente. Depressive symptoms tend to resurface after a few months of injections, indicating that BoNT may be more effective when used as complementary therapy. Meta-analysis results demonstrate that BTX-A injections have been effective as an adjuvant treatment in Major Depressive Disorder (MDD). BTX-A presents itself as a highly relevant alternative for the treatment of depression. However, further research is needed to provide a deeper.